(3JCSjS GdfXQs - (3YHO Gddg Hf YeQHf YjSi, CHh RjO GdOHhSj GdMfaj,J (B430 (3g` s
(3ChdgG (B:s
(3CWGd Gddg HbGA CejQ GdeDefjf hCOGe dg GdYR aj JeGe ef GdfYeI hOhGe ef GdcQGeI s
(3BNQgG (B:s
(3heGJ ef Pdc GdbWY Gfg jLjH Ydjg GdOjI GdcGedI hGddg JYGdi CYde HGdUhGH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B109 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B96s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3abg Mfai e (B111) s
Keywords: (3Gdabg GdMfajs